Preparation process of resin-derived carbon composite biomass-based silicon-carbon negative electrode material

CN122916100APending Publication Date: 2026-10-16CHENGDU HERUI ZHICE ENTERPRISE MANAGEMENT CONSULTING PARTNERSHIP (LLP)
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611168160.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-03
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

对于消费电子、电动工具等领域电芯厂而言,涂布一致性和批次稳定性是其对负极材料的核心要求,上述问题因此成为制约该类硅碳负极材料规模化量产应用的重要产业化障碍

Benefits of technology

本发明提供的树脂衍生碳复合生物质基硅碳负极材料的制备工艺,能够有效改善背景技术中提及的技术问题,具体作用如下:

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application discloses a preparation process of resin-derived carbon composite biomass-based silicon-carbon negative electrode material and belongs to the technical field of lithium ion battery negative electrode materials. The process comprises the following steps: dispersing biomass source nano silicon particles in a solution containing a coal-based carbon precursor, drying to form a coal-based carbon precursor layer, and performing pre-oxidation treatment to obtain first precursor particles; impregnating a polyvinyl alcohol solution to form a sacrificial isolation layer; coating a resin carbon precursor on the surface of the sacrificial isolation layer to obtain second precursor particles, wherein the main pyrolysis temperature interval of the coal-based carbon precursor is higher than that of the resin carbon precursor; and performing one-time co-carbonization under an inert atmosphere, and performing segmented temperature control to make the outer layer of resin carbon solidify first, and the inner layer of coal-based carbon pyrolyze later under the constraint of the outer layer, thereby in-situ constructing a radial gradient carbon matrix structure with a loose and porous inner layer and a relatively dense outer layer. The pyrolysis mismatch defect is converted into an active means for constructing a gradient structure, and the cycle stability and coating process consistency of the obtained material are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of lithium-ion battery anode material technology, specifically a preparation process for a resin-derived carbon composite biomass-based silicon-carbon anode material. Background Technology

[0002] Silicon, with its theoretical specific capacity of up to 4200 mAh / g, is a crucial anode active material for improving the energy density of lithium-ion batteries. Currently, the increasing demands for battery life and fast charging performance in high-end smartphones, laptops, power tools, drones, and other terminal applications are driving the exploration of high-capacity anode materials. However, silicon undergoes approximately 300% volume change during lithium insertion / extraction, which easily leads to particle pulverization, electrode structure damage, and repeated rupture and regeneration of the solid electrolyte interphase (SEI) film, severely limiting its practical application.

[0003] To alleviate the aforementioned problems, dispersing nano-silicon particles within a carbon matrix, with the carbon matrix buffering volume expansion and maintaining the integrity of the electrode structure, thus forming silicon-carbon composite anode materials, has become the mainstream technical approach. The carbon matrix serves to provide a mechanical buffer framework and construct electron and ion transport networks. Among various carbon sources, resin-derived carbon (such as phenolic resin carbon and epoxy resin carbon) is often used as the outer protective shell or internal support framework of silicon-carbon composite particles due to its high residual carbon content and dense structure after carbonization. However, pure resin carbon suffers from high raw material costs and concentrated stress during carbonization shrinkage, making its use alone insufficient in terms of economy and interfacial stability.

[0004] One direction explored by the industry in response is to combine coal-based carbon sources with resin carbon to reduce costs. Coal-based carbon sources—including coal tar pitch, coal-derived activated carbon, and their processed products—are widely available and have high carbon content, giving them an advantage in cost control. Theoretically, the composite carbon matrix route of "resin carbon + coal-based carbon" can balance mechanical integrity and economic efficiency.

[0005] However, the core obstacle to this approach lies in the significant mismatch in the pyrolysis behavior of the two carbon sources during co-carbonization. Coal tar pitch, a representative carbon source, primarily experiences pyrolysis weight loss, melt flow, and volume shrinkage in the 400-700℃ range; while common resin carbon precursors (such as phenolic resins) primarily experience pyrolysis weight loss and structural rearrangement in the 300-500℃ range, with their carbonization process extending to higher temperatures. During co-carbonization, when the temperature reaches the pyrolysis range of the resin carbon, the resin carbon component begins to undergo significant chemical structural rearrangement and volume shrinkage. At this point, the coal-based carbon component is still in a molten or semi-coke state, and the small-molecule gases continuously released from its decomposition need to diffuse outward through the pre-solidified resin carbon matrix. This asynchronous evolution effect creates interfacial microcracks and uncontrollable pore structures within the composite carbon material, leading to deterioration of both the mechanical integrity and ion transport uniformity of the carbon matrix. The resulting uncontrollable carbon matrix structure has two main impacts: At the material performance level, microcracks and uneven pores weaken the carbon matrix's ability to uniformly constrain the volume expansion of silicon nuclei, and localized stress concentration accelerates the cyclic decay of silicon-carbon particles. At the industrialization level, the inconsistency between the carbon matrix's pore structure and surface chemistry leads to abnormally sensitive compatibility of the same batch of silicon-carbon anode powder with solvents and binders during downstream cell manufacturing. In coating lines across different seasons or regions, the rheological behavior of the slurry drifts, resulting in uneven coating density and drying cracking. This problem is not prominent in single-carbon-source silicon-carbon systems, but it is amplified in composite carbon matrices of "resin-carbon + coal-based carbon" due to differences in the surface functional groups and pore structures of the two carbon materials. For cell manufacturers in consumer electronics, power tools, and other fields, coating consistency and batch stability are core requirements for anode materials. Therefore, the aforementioned problems have become significant industrialization obstacles restricting the large-scale mass production and application of this type of silicon-carbon anode material.

[0006] In addition, the trace amounts of residual ash in coal-based carbon may cause local structural inhomogeneity of the surrounding carbon matrix during carbonization, and the oriented adsorption of carbon precursor molecules by silanol groups contained in the natural oxide layer on the surface of biomass silica particles are also interfering factors that need to be taken into account in this system.

[0007] In summary, in the composite carbon matrix route of "resin carbon + coal-based carbon", how to reduce the adverse effects of asynchronous pyrolysis evolution during the co-carbonization of the two carbon sources on the integrity and batch consistency of the carbon matrix is ​​an urgent problem to be solved in order to improve the cycle stability and industrial applicability of this type of silicon-carbon anode material. Summary of the Invention

[0008] The purpose of this invention is to provide a preparation process for resin-derived carbon composite biomass-based silicon-carbon anode materials. This process, through the synergistic design of inverted coating sequence, polyvinyl alcohol sacrificial isolation layer, and segmented co-carbonization temperature regime, transforms the problem of pyrolysis behavior mismatch in "resin carbon + coal-based carbon" co-carbonization, which is usually regarded as a process defect, into an active means of in-situ construction of radial gradient carbon matrix, thereby improving the cycle stability and coating process consistency of silicon-carbon anode materials.

[0009] The objective of this invention is achieved through the following technical solution: A preparation process for a resin-derived carbon composite biomass-based silicon-carbon anode material includes the following steps: S1. Biomass-sourced nano-silicon particles are dispersed in a solution containing a coal-based carbon precursor, and dried to form a coal-based carbon precursor layer on the surface of the biomass-sourced nano-silicon particles; the coal-based carbon precursor layer is pre-oxidized to obtain the first precursor particles. S2. The first precursor particles are immersed in a polyvinyl alcohol solution, removed and dried to form a polyvinyl alcohol sacrificial isolation layer on the surface of the coal-based carbon precursor layer; S3. The resin carbon precursor is dispersed in a solvent, and the product obtained in step S2 is added. After mixing and drying, a resin carbon precursor layer is formed on the surface of the polyvinyl alcohol sacrificial isolation layer to obtain the second precursor particles. The main pyrolysis temperature range of the coal-based carbon precursor is higher than that of the resin carbon precursor. S4. The second precursor particles are subjected to a co-carbonization treatment under an inert atmosphere. The heating regime of the co-carbonization treatment includes at least: holding at a first temperature range, and then continuing to heat to a second temperature range and holding at that temperature. The first temperature range corresponds to the main pyrolysis temperature range of the resin carbon precursor, and the second temperature range corresponds to the main pyrolysis temperature range of the coal-based carbon precursor.

[0010] As some possible implementations of this application, in step S1, the biomass-sourced nano-silicon particles are prepared by carbonizing at least one biomass raw material selected from rice husks, bamboo leaves, and straw, followed by magnesium thermal reduction or carbothermic reduction. The average particle size is 30-200 nm, which ensures the electrochemical activity of the silicon particles while avoiding the problems of excessive specific surface area and increased side reactions caused by excessively small particle size. The coal-based carbon precursor is selected from at least one of medium-temperature coal tar pitch and coal tar pitch, with a softening point of 75-100℃ and a main pyrolysis temperature range of 400-700℃. The mass ratio of the coal-based carbon precursor to the biomass-sourced nano-silicon particles is 1:0.5~5.

[0011] As some possible implementations of this application, in step S3, the resin carbon precursor is selected from at least one of phenolic resin, epoxy resin, and urea-formaldehyde resin, and its main pyrolysis temperature range is 300-500℃, forming a clear gradient difference with the pyrolysis temperature range of the inner coal-based carbon precursor; in step S3, the mass ratio of the resin carbon precursor to the first precursor particles obtained in step S1 is 1:0.5~3.

[0012] As some possible implementations of this application, in step S4, the first temperature range is controlled at 300-500℃ for 1-4 hours, and the second temperature range is controlled at 600-800℃ for 2-6 hours. This temperature regime matches the pyrolysis behavior of the outer resin carbon and the inner coal-based carbon, providing a sufficient time window for asynchronous evolution. The heating rate from room temperature to the first temperature range is controlled at 1-3℃ / min, and the heating rate from the first temperature range to the second temperature range is controlled at 3-5℃ / min. The slow heating in the first stage is conducive to the full pyrolysis and shaping of the outer resin carbon, while the rapid heating in the later stage helps the inner coal-based carbon to complete the cracking under constrained conditions.

[0013] As some possible implementations of this application, the heating rate from room temperature to the first temperature range is 1-3℃ / min, and the heating rate from the first temperature range to the second temperature range is 3-5℃ / min.

[0014] As one possible implementation of this application, step S1, before compounding the coal-based carbon precursor, further includes: heat-treating the biomass-sourced nano-silicon particles at 200-300°C for 0.5-3 hours under an inert atmosphere. This method can cause some of the silanol groups in the natural oxide layer on the surface of the silicon particles to undergo condensation and dehydration, reducing the orientation adsorption of the carbon precursor by the hydroxyl groups on the silicon surface, and reducing the formation of an excessively dense carbon layer with poor ion permeability at the silicon-carbon interface after carbonization.

[0015] As some possible implementations of this application, in steps S1 and S3, the drying treatment is one of spray drying, stirred evaporation or liquid phase deposition; the pre-oxidation treatment in step S1 is to treat at 200-300℃ for 0.5-2h in air or oxygen-containing atmosphere, which can make the coal-based carbon precursor layer insoluble in subsequent solvents, while avoiding excessive oxidation that would reduce the residual carbon rate after carbonization.

[0016] As some possible implementations of this application, in step S2, the mass concentration of polyvinyl alcohol in the polyvinyl alcohol solution is 0.5%-3%; and the thickness of the polyvinyl alcohol sacrificial isolation layer after drying is 5-20 nm.

[0017] As one possible implementation method of this application, the polyvinyl alcohol is a partially alcoholyzed polyvinyl alcohol with a saponification degree of 85%-90%. The small amount of oxygen-containing residual carbon remaining after pyrolysis and gasification of this type of polyvinyl alcohol under an inert atmosphere can complex with metal sites in the ash on the surface of the coal-based carbon precursor, passivating the catalytic activity of the metal components in the ash during the co-carbonization process, inhibiting their catalytic graphitization effect, reducing the formation of discrete graphite microcrystal regions, and improving the uniformity of lithium-ion transport in the carbon matrix.

[0018] As one possible implementation of this application, the polyvinyl alcohol solution further contains boric acid, the mass of which is 1%–5% of the mass of the polyvinyl alcohol. In this embodiment, boric acid is uniformly distributed on the surface of the coal-based carbon precursor layer along with the polyvinyl alcohol film. During the high-temperature co-carbonization stage, boron diffuses into the adjacent inner carbon layer and is doped into the carbon matrix, playing a role in pinning the microstructure of the carbon layer. This enhances the stability of the cyclic structure of the loose carbon pore walls in the inner layer and delays the gradual collapse of the pore walls caused by repeated expansion and contraction of silicon nuclei during long cycles.

[0019] Compared with the prior art, the beneficial effects of the present invention are: The preparation process of the resin-derived carbon composite biomass-based silicon-carbon anode material provided by this invention can effectively improve the technical problems mentioned in the background art, and its specific effects are as follows: In step S1, biomass-sourced nano-silicon particles are first dispersed in a solution containing a coal-based carbon precursor. After drying, a coal-based carbon precursor layer is formed on the surface of the silicon particles, followed by pre-oxidation treatment. Pre-oxidation causes the coal-based carbon precursor layer to undergo oxidative cross-linking, preventing it from dissolving or swelling when it comes into contact with the organic solvent of the resin carbon precursor in the subsequent step S3. This ensures the integrity of the bilayer precursor structure during subsequent solvent contact and avoids the inability to form a radial gradient structure after carbonization due to the mutual solubility and mixing of the two carbon precursor layers.

[0020] In step S2, the pre-oxidized first precursor particles are immersed in a polyvinyl alcohol (PVA) solution, removed, and dried to form a PVA sacrificial isolation layer on the surface of the coal-based carbon precursor layer. This isolation layer physically separates the coal-based carbon precursor layer from the resin carbon precursor layer in the subsequent step S3, preventing excessive cross-linking reactions between the oxygen-containing functional groups introduced by pre-oxidation and the pyrolysis free radicals of the resin carbon in the early stages of co-carbonization. During co-carbonization in step S4, PVA gradually pyrolyzes and gasifies within the range of 250-500℃. Its main weight loss stage occurs earlier than the structural stabilization stage of the resin carbon, allowing it to escape from the interlayer before the resin carbon is fully cured, leaving only trace amounts of oxygen-containing residual carbon. This has little impact on the overall composition of the carbon matrix, but it can play an auxiliary role in passivating ash catalytic sites. Since the resin carbon is still in the early stage of pyrolysis and has a high viscosity during the main gasification stage of PVA, significant molecular-level mixing does not occur between the inner and outer carbon precursor layers. This is beneficial for forming a radial gradient carbon matrix structure with decreasing porosity and increasing density from the inside to the outside after co-carbonization.

[0021] In step S3, the resin carbon precursor is coated onto the surface of the polyvinyl alcohol sacrificial isolation layer, forming a three-layer precursor structure: "inner coal-based carbon precursor - middle polyvinyl alcohol isolation layer - outer resin carbon precursor". The main pyrolysis temperature range of the coal-based carbon precursor (400-700℃) is higher than that of the resin carbon precursor (300-500℃). This difference in pyrolysis temperature range is a prerequisite for constructing a radial gradient carbon matrix using asynchronous evolution in the subsequent step S4.

[0022] In step S4, the second precursor particles undergo a co-carbonization process under an inert atmosphere, employing a segmented temperature control regime. The first temperature range corresponds to the main pyrolysis temperature zone of the outer resin carbon precursor. During this stage, the outer resin carbon first completes the main pyrolysis reaction and structural stabilization, forming a relatively continuous outer carbon skeleton. The second temperature range corresponds to the main pyrolysis temperature zone of the inner coal-based carbon precursor. Under the constraint of the preliminarily sculpted outer carbon skeleton, the inner coal-based carbon completes pyrolysis and volume shrinkage, limiting the outward diffusion rate of its pyrolysis gases and retaining more pores within the inner carbon matrix. Thus, in this single co-carbonization process, utilizing the inherent differences in the pyrolysis behavior of the two carbon sources, a radial gradient carbon matrix structure of "relatively dense outer layer and loose porous inner layer" is constructed in situ. The dense outer carbon shell reduces the direct contact between the electrolyte and the silicon surface, while the loose porous inner structure provides a buffer space for the volume expansion of the silicon core, reducing stress concentration on the carbon shell.

[0023] The resin-derived carbon composite biomass-based silicon-carbon anode material prepared by the above process has a radial gradient carbon matrix structure with an inner layer of loose, porous carbon as a buffer layer and an outer layer of relatively dense carbon as a constraining shell. This structure transforms the problem of pyrolysis mismatch in the co-carbonization of "resin carbon + coal-based carbon," which is usually considered a process defect, into an active means of constructing a radial gradient carbon matrix in situ. The outer dense carbon shell reduces the direct contact between the electrolyte and the silicon surface, while the inner loose, porous structure provides buffer space for the volume expansion of the silicon core, resulting in improved cycle stability when the material is used as a lithium-ion battery anode. At the same time, the improved controllability of the carbon matrix structure makes the surface chemical state and pore structure of the powder in the same batch more consistent, which helps to reduce the drift of slurry rheological behavior caused by changes in environmental humidity during coating and slurry preparation in downstream cell factories, and improves the consistency of coating processes between batches. Detailed Implementation

[0024] Example 1 Step S1: Take 5g of biomass-derived nano-silicon particles and heat-treat them at 250℃ for 1h under an inert atmosphere. Disperse the heat-treated biomass-derived nano-silicon particles in 50mL of tetrahydrofuran solution containing medium-temperature coal tar pitch (softening point approximately 90℃, main pyrolysis temperature range 400-700℃). The concentration of medium-temperature coal tar pitch is 0.1g / mL, and the mass ratio of coal-based carbon precursor to biomass-derived nano-silicon particles is 1:1. After stirring and dispersing for 30min, remove the solvent by spray drying. The inlet air temperature of the spray drying is 140℃, and the outlet air temperature is 80℃. The spray drying system adopts an explosion-proof design. A coal-based carbon precursor layer is formed on the surface of the biomass-derived nano-silicon particles. Place the dried powder in a muffle furnace and pre-oxidize it at 250℃ for 1h under an air atmosphere. During the pre-oxidation treatment, the powder is mechanically stirred and agitated to obtain the first precursor particles.

[0025] The preparation method of the above-mentioned biomass-derived silicon nanoparticles is as follows (other examples and comparative examples were prepared using this method): Rice husks were washed three times with deionized water and dried in an 80℃ forced-air drying oven for 12 hours. The dried rice husks were then pre-carbonized in air at a temperature of 600℃ / min for 2 hours to obtain rice husk carbon. The rice husk carbon was ground to a particle size of less than 100 mesh and mixed evenly with magnesium powder at a mass ratio of 1:1. The mixture was placed in a tube furnace and heated to 700℃ at a temperature of 5℃ / min for 4 hours in an argon atmosphere to carry out a magnesothermic reduction reaction. After the reaction product was naturally cooled to room temperature, it was washed with 1 mol / L hydrochloric acid solution for 4 hours with stirring to remove magnesium oxide and unreacted magnesium powder. It was then washed with deionized water until the filtrate was neutral, and finally washed with hydrofluoric acid solution to remove unreacted silicon dioxide. The mixture was washed again with deionized water until neutral and dried in an 80℃ vacuum drying oven for 12 hours to obtain biomass-derived nano-silicon particles with an average particle size of approximately 100 nm.

[0026] Step S2: Prepare a 1.5% (w / w) polyvinyl alcohol aqueous solution (the polyvinyl alcohol is a partially hydrolyzed form with a saponification degree of 88%), immerse the first precursor particles obtained in S1 in the solution, stir for 10 min, remove and dry in a 60℃ forced-air drying oven for 2 h to form a polyvinyl alcohol sacrificial isolation layer with a thickness of about 10 nm on the surface of the coal-based carbon precursor layer.

[0027] Step S3: Dissolve phenolic resin (mainly in the pyrolysis temperature range of 300-500℃) in anhydrous ethanol to prepare a phenolic resin solution with a concentration of 0.08 g / mL. Add the product obtained in S2 to this solution, with a mass ratio of phenolic resin to first precursor particles of 1:1. After stirring and mixing for 30 min, remove the solvent by stirring and evaporating at 60℃. A resin carbon precursor layer is formed on the surface of the polyvinyl alcohol sacrificial isolation layer, resulting in second precursor particles with a three-layer structure of "inner coal-based carbon precursor - middle polyvinyl alcohol isolation layer - outer resin carbon precursor".

[0028] Step S4: The second precursor particles obtained in S3 were placed in a tube furnace and subjected to a co-carbonization treatment under an argon atmosphere. The heating regime was as follows: the temperature was increased from room temperature to 400℃ at a rate of 2℃ / min and held for 2 hours; then the temperature was increased from 400℃ to 700℃ at a rate of 4℃ / min and held for 4 hours. After natural cooling to room temperature, the resin-derived carbon composite biomass-based silicon-carbon anode material was obtained.

[0029] Example 2 This embodiment is based on Example 1, with only some parameters adjusted. All other raw materials, preparation methods, and operating procedures not mentioned are the same as in Example 1. Specific parameter adjustments are as follows: In step S1, the amount of biomass-derived nano-silicon particles remains 5g, but the heat treatment conditions for the silicon particles are changed to 200℃ for 3 hours. The coal-based carbon precursor is selected as medium-temperature coal tar pitch with a softening point of about 75℃, and the mass ratio of the coal-based carbon precursor to the biomass-derived nano-silicon particles is changed to 1:0.5. The drying method is changed to stirring evaporation with an evaporation temperature of 80℃. The pre-oxidation conditions are changed to 200℃ for 2 hours, and the powder is stirred and turned during the pre-oxidation process.

[0030] In step S2, the mass concentration of the polyvinyl alcohol solution is changed to 0.5%, the degree of polyvinyl alcohol saponification is changed to 85%, and the thickness of the resulting sacrificial isolation layer is approximately 5 nm.

[0031] In step S3, the resin carbon precursor is replaced with epoxy resin (mainly pyrolysis temperature range 300-500℃), dissolved in acetone, and an epoxy resin solution with a concentration of 0.1 g / mL is prepared; the mass ratio of epoxy resin to the first precursor particles is changed to 1:0.5; the coating method is changed to liquid phase deposition, and the material is allowed to stand and dry after deposition.

[0032] In step S4, the heating regime is changed to: heating from room temperature to 300℃ at 1℃ / min and holding for 4 hours; then heating from 300℃ to 600℃ at 3℃ / min and holding for 6 hours.

[0033] Example 3 This embodiment is based on Example 1, with only some parameters adjusted. All other raw materials, preparation methods, and operating procedures not mentioned are the same as in Example 1. Specific parameter adjustments are as follows: In step S1, the amount of biomass-derived nano-silicon particles fed is still 5g, and the heat treatment conditions for the silicon particles are changed to 300℃ for 0.5h; the coal-based carbon precursor is selected as medium-temperature coal tar pitch with a softening point of about 100℃, and the mass ratio of the coal-based carbon precursor to the biomass-derived nano-silicon particles is changed to 1:5; the pre-oxidation conditions are changed to 300℃ for 0.5h, and the powder is stirred and turned during the pre-oxidation process.

[0034] In step S2, the mass concentration of the polyvinyl alcohol solution is changed to 3%, the degree of polyvinyl alcohol saponification is changed to 90%, and the thickness of the resulting sacrificial isolation layer is approximately 20 nm.

[0035] In step S3, the resin carbon precursor is replaced with urea-formaldehyde resin (main pyrolysis temperature range 300-500℃), which is dissolved in a mixed solvent of ethanol and water at a volume ratio of 7:3 to prepare a urea-formaldehyde resin solution with a concentration of 0.15 g / mL; the mass ratio of urea-formaldehyde resin to the first precursor particles is changed to 1:3; the drying method is changed to stirring evaporation, and the evaporation temperature is 70℃.

[0036] In step S4, the heating regime is changed to: heating from room temperature to 500℃ at 3℃ / min and holding for 1 hour; then heating from 500℃ to 800℃ at 5℃ / min and holding for 2 hours.

[0037] Example 4 This embodiment is based on Example 1, except that the composition of the polyvinyl alcohol solution in step S2 is adjusted. All other raw materials, raw material preparation methods, and operation steps are the same as in Example 1.

[0038] The specific adjustments are as follows: In step S2, when preparing the polyvinyl alcohol solution, in addition to polyvinyl alcohol (partially hydrolyzed form with a saponification degree of 88%), boric acid is added. The mass of boric acid is 3% of the mass of polyvinyl alcohol. After stirring and dissolving evenly, it is used to impregnate the first precursor particles. The remaining operations are the same as in Example 1.

[0039] Comparative Example 1 Compared to Example 1, the pre-oxidation treatment is omitted in step S1. That is, after spray drying, a coal-based carbon precursor layer is formed on the surface of the biomass-sourced nano-silicon particles, and no pre-oxidation treatment is performed. The particles are directly used as the first precursor particles for subsequent steps. All other raw materials, raw material preparation methods, operating steps, and parameters are the same as in Example 1.

[0040] Comparative Example 2 Compared to Example 1, step S2 is omitted, meaning the first precursor particles obtained in S1 are not impregnated with the polyvinyl alcohol solution and are directly coated with the resin carbon precursor in step S3. All other raw materials, preparation methods, operating procedures, and parameters are the same as in Example 1.

[0041] Comparative Example 3 Compared to Example 1, step S4 does not involve segmented temperature control; the temperature is directly increased from room temperature to 800°C at a rate of 5°C / min and held at that temperature for 6 hours. All other raw materials, preparation methods, operating procedures, and parameters are consistent with Example 1.

[0042] Comparative Example 4 Compared to Example 1, the carbon source types in steps S1 and S3 are interchanged. Specifically, in step S1, the coal-based carbon precursor is replaced with phenolic resin (main pyrolysis temperature range 300-500℃); in step S3, the resin carbon precursor is replaced with medium-temperature coal tar pitch (main pyrolysis temperature range 400-700℃). All other raw materials, preparation methods, operating procedures, and parameters remain the same as in Example 1.

[0043] Comparative Example 5 Compared to Example 1, in step S2, the polyvinyl alcohol solution is replaced with an aqueous glucose solution of the same mass concentration, while the rest of the operations remain unchanged. All other raw materials, preparation methods, operating steps, and parameters are consistent with Example 1.

[0044] Comparative Example 6 Compared to Example 1, in step S2, the partially hydrolyzed polyvinyl alcohol with a saponification degree of 88% is replaced with fully hydrolyzed polyvinyl alcohol with a saponification degree of 98% (which leaves almost no oxygen-containing carbon residue after pyrolysis under an inert atmosphere). The other raw materials, raw material preparation methods, operating steps, and parameters are the same as in Example 1.

[0045] Comparative Example 7 Compared to Example 1, in step S1, the biomass-sourced nano-silicon particles are not subjected to heat treatment. Instead, 5g of biomass-sourced nano-silicon particles are directly dispersed in a tetrahydrofuran solution containing medium-temperature coal tar pitch. The remaining raw materials, raw material preparation methods, operating steps, and parameters are the same as in Example 1.

[0046] Experimental Example This experiment tested the electrochemical performance of coin half-cells and the batch consistency of the slurry. All samples from Examples 1-4 and Comparative Examples 1-7 were included. All samples were prepared with negative electrode sheets and assembled into cells under the same conditions. Three parallel replicate experiments were simultaneously set up for each sample group. The average of the three parallel tests was taken as the final test result, with a relative standard deviation (RSD) ≤ 5%. The test results are shown in Table 1. Specific tests are as follows: Negative electrode preparation: Each sample was mixed with conductive carbon black (Super P) and polyacrylic acid binder at a mass ratio of 80:10:10, using deionized water as solvent, and stirred in a planetary mixer at 1500 r / min for 2 h to prepare a slurry. The slurry was coated onto a 9 μm thick copper foil using a doctor blade, with the coating thickness controlled at 100 μm, and dried in a vacuum drying oven at 80℃ for 4 h. The dried electrode was then rolled to a compaction density of approximately 1.0 g / cm³ using a roller press, and punched into round discs with a diameter of 12 mm to serve as the negative electrode.

[0047] Coin cell assembly: Using the prepared negative electrode as the working electrode, lithium metal sheet as the counter electrode and reference electrode, Celgard 2400 polypropylene membrane as the separator, and 1 mol / L LiPF6 dissolved in a mixed solvent of ethylene carbonate (EC), dimethyl carbonate (DMC), and ethyl methyl carbonate (EMC) (volume ratio 1:1:1) as the electrolyte, CR2032 coin cells were assembled in an argon glove box (water content <0.1 ppm, oxygen content <0.1 ppm).

[0048] Cycle stability test: After the assembled coin cell half-cells were left to stand at room temperature for 12 hours, constant current charge-discharge tests were performed using the Blue Battery Testing System. The voltage range was 0.01-1.5V (vs. Li / Li). + The first three cycles were activated with a current density of 0.1C, and from the fourth cycle onwards, charge-discharge cycles were performed with a current density of 0.5C. The initial discharge specific capacity and initial charge specific capacity were recorded, and the initial coulombic efficiency (initial charge specific capacity / initial discharge specific capacity × 100%) was calculated. The charge specific capacity of the third cycle and the discharge specific capacity of the 200th cycle were recorded, and the capacity retention rate of the 200-cycle cycle (discharge specific capacity of the 200th cycle / discharge specific capacity of the third cycle × 100%) was calculated.

[0049] Batch consistency test of slurry: Three parallel samples of the same sample were taken and prepared according to the same formula and process under environmental conditions of relative humidity of 30%, 50%, and 70%, respectively. The slurry was measured at a shear rate of 10 s⁻¹ at 25°C using a rotational rheometer. - ¹The viscosity is used to calculate the maximum relative deviation of the viscosity of the three slurries [maximum viscosity - minimum viscosity) / average viscosity × 100%].

[0050] Table 1. Results of Electrochemical Performance and Batch Consistency Tests for Each Sample Note: Capacity retention rate after 200 cycles is calculated based on the specific capacity at the 3rd charge cycle. "-" indicates that this metric was not tested.

[0051] As shown in Table 1: The samples obtained in Examples 1-3 effectively solved the problem of uncontrollable carbon matrix structure caused by the mismatch of pyrolysis behavior in the co-carbonization of "resin carbon + coal-based carbon", as well as the industrialization obstacles such as insufficient cycle stability and poor consistency of coating process between batches. The initial discharge specific capacity was ≥1489mAh / g, the initial charge specific capacity was ≥1266mAh / g, and the initial coulombic efficiency was ≥85.7%, indicating that the carbon matrix structure was intact and the outer carbon shell effectively reduced the direct contact between the electrolyte and the silicon surface, thus reducing irreversible lithium consumption during the first cycle. The capacity retention rate after 200 cycles was ≥81.2%, indicating that the loose porous structure of the inner layer provided an effective buffer space for the volume expansion of the silicon core, reducing stress concentration on the carbon shell during long cycles and better maintaining the mechanical integrity of the carbon matrix. The maximum viscosity deviation of the slurry under different humidity was ≤18%, indicating that the improved controllability of the carbon matrix structure made the surface chemical state and pore structure of the same batch of powder more consistent, reducing the sensitivity to the humidity of the production environment during coating and slurry preparation in downstream cell factories, which is conducive to improving the consistency of coating processes between batches.

[0052] Example 4 introduces boric acid doping based on Example 1, which further improves the capacity retention rate after 200 cycles, indicating that boron doping helps to enhance the cycle structure stability of the inner carbon pore wall and has no negative impact on batch consistency.

[0053] In Comparative Example 1, omitting the pre-oxidation step resulted in the coal-based carbon precursor layer being partially dissolved by the organic solvent in step S3. The two carbon precursor layers were miscible and mixed, failing to form a radial gradient structure after carbonization. This disrupted the integrity of the carbon matrix, leading to a significant decrease in initial coulombic efficiency, capacity retention, and slurry consistency. In Comparative Example 2, omitting the PVA sacrificial isolation layer resulted in excessive cross-linking of the oxygen-containing functional groups on the surface of the pre-oxidized coal-based carbon with the pyrolysis radicals of the resin carbon, forming a dense transition layer at the interface that hinders lithium-ion transport. In Comparative Example 3, without segmented temperature control, the two carbon sources pyrolyzed simultaneously in similar temperature ranges. Before the outer resin carbon layer was fully cured and shaped, the inner coal-based carbon layer began to crack and produce gas, making it impossible to construct a radial gradient carbon matrix using asynchronous evolution. In Comparative Example 4, by swapping the types of inner and outer carbon sources, the inner resin carbon layer cured first at a lower temperature, while the outer coal-based carbon layer melted and pyrolyzed at a higher temperature. Due to the lack of a rigid outer shell constraint, the pyrolysis gas from the outer layer of coal-based carbon can escape directly to the outside. Simultaneously, its own melting flow and contraction cause the final carbon matrix to tend towards densification, failing to construct a radial gradient structure that is loose inside and dense outside. In Comparative Example 5, after replacing PVA with glucose, glucose, as a carbon precursor, does not vaporize and escape during co-carbonization. Instead, it carbonizes to form a dense carbon layer remaining between the two layers. This non-sacrificial carbon layer not only fails to provide buffer space but also increases interfacial impedance, hindering the rapid transport of lithium ions. Therefore, it fails to perform the sacrificial isolation function of the present invention. In Comparative Example 6, after replacing partially alcoholyzable PVA with fully alcoholyzable PVA, the fully alcoholyzable PVA leaves almost no oxygen-containing residual carbon after pyrolysis. It cannot complex and passivate the metal sites in the ash on the surface of coal-based carbon, and the ash-catalyzed graphitization effect is not sufficiently suppressed, resulting in a decrease in capacity retention compared to Example 1.

[0054] In addition, to verify the radial gradient carbon matrix structure of the material obtained in this invention, the following supplementary tests were conducted: (1) Comparison test of tapped density The samples obtained from Example 1 and Comparative Example 4 were tested for their tap density according to GB / T 5162-2021. The tap density of the sample from Example 1 was 0.75 g / cm³, while that of the sample from Comparative Example 4 was 0.88 g / cm³. The tap density of Example 1 was significantly lower than that of Comparative Example 4. This is because the loose and porous inner layer structure of Example 1 reduced the overall particle density, while in Comparative Example 4, due to the exchange of carbon sources, the inner layer resin carbon cured first, and the outer layer coal-based carbon pyrolysis gas escaped freely, resulting in a more compact carbon matrix and a relatively higher tap density. This difference is consistent with the expected radial gradient structure of "loose inside and dense outside".

[0055] (2) Specific surface area comparison test Samples obtained from Example 1 and Comparative Example 2 were degassed at 200°C for 6 hours under vacuum before testing, followed by nitrogen adsorption-desorption testing. The specific surface area was calculated using the BET multi-point method. The BET specific surface area of ​​Example 1 was 185 m² / g, while that of Comparative Example 2 was 132 m² / g. The specific surface area of ​​Example 1 was significantly higher than that of Comparative Example 2. In Comparative Example 2, due to the omission of the PVA sacrificial isolation layer, the oxygen-containing functional groups on the surface of the pre-oxidized coal-based carbon directly contacted the pyrolysis free radicals of the resin carbon, resulting in excessive cross-linking. A dense transition layer was formed at the interface, and the internal pores were closed, thus reducing the specific surface area. The higher specific surface area of ​​Example 1 is attributed to the effective prevention of excessive cross-linking by the PVA sacrificial isolation layer, which, after pyrolysis and gasification, contributed additional micropores and mesopores to the inner carbon matrix, consistent with the loose and porous structural characteristics of the inner layer.

Claims

1. A preparation process for a resin-derived carbon composite biomass-based silicon-carbon anode material, characterized in that, Includes the following steps: S1. Biomass-sourced nano-silicon particles are dispersed in a solution containing a coal-based carbon precursor, and dried to form a coal-based carbon precursor layer on the surface of the biomass-sourced nano-silicon particles; the coal-based carbon precursor layer is pre-oxidized to obtain the first precursor particles. S2. The first precursor particles are immersed in a polyvinyl alcohol solution, removed and dried to form a polyvinyl alcohol sacrificial isolation layer on the surface of the coal-based carbon precursor layer; S3. The resin carbon precursor is dispersed in a solvent, and the product obtained in step S2 is added. After mixing and drying, a resin carbon precursor layer is formed on the surface of the polyvinyl alcohol sacrificial isolation layer to obtain the second precursor particles. The main pyrolysis temperature range of the coal-based carbon precursor is higher than that of the resin carbon precursor. S4. The second precursor particles are subjected to a co-carbonization treatment under an inert atmosphere. The heating process of the co-carbonization treatment includes at least: holding at a first temperature range, and then continuing to heat to a second temperature range and holding at that temperature. The first temperature range corresponds to the main pyrolysis temperature range of the resin carbon precursor, and the second temperature range corresponds to the main pyrolysis temperature range of the coal-based carbon precursor.

2. The preparation process according to claim 1, characterized in that, In step S1, the biomass-sourced nano-silicon particles are prepared by carbonizing at least one biomass raw material selected from rice husks, bamboo leaves, and straw, followed by magnesothermic reduction or carbothermic reduction, with an average particle size of 30-200 nm; the coal-based carbon precursor is selected from at least one of medium-temperature coal tar pitch and coal tar pitch, with a softening point of 75-100℃ and a main pyrolysis temperature range of 400-700℃; the mass ratio of the coal-based carbon precursor to the biomass-sourced nano-silicon particles is 1:0.5~5.

3. The preparation process according to claim 1, characterized in that, In step S3, the resin carbon precursor is selected from at least one of phenolic resin, epoxy resin, and urea-formaldehyde resin, and its main pyrolysis temperature range is 300-500℃; in step S3, the mass ratio of the resin carbon precursor to the first precursor particles obtained in step S1 is 1:0.5~3.

4. The preparation process according to claim 1, characterized in that, In step S4, the first temperature range is 300-500℃, and the heat preservation time in the first temperature range is 1-4h; the second temperature range is 600-800℃, and the heat preservation time in the second temperature range is 2-6h.

5. The preparation process according to claim 4, characterized in that, The heating rate from room temperature to the first temperature range is 1-3℃ / min, and the heating rate from the first temperature range to the second temperature range is 3-5℃ / min.

6. The preparation process according to claim 1, characterized in that, In step S1, before compounding the coal-based carbon precursor, the method further includes: heat-treating the biomass-sourced nano-silicon particles at 200-300℃ for 0.5-3 hours under an inert atmosphere.

7. The preparation process according to claim 1, characterized in that, In steps S1 and S3, the drying process is one of spray drying, stirred evaporation, or liquid phase deposition; the pre-oxidation process in step S1 is to treat at 200-300℃ for 0.5-2 hours in air or an oxygen-containing atmosphere.

8. The preparation process according to claim 1, characterized in that, In step S2, the mass concentration of polyvinyl alcohol in the polyvinyl alcohol solution is 0.5%–3%; the thickness of the polyvinyl alcohol sacrificial isolation layer after drying is 5–20 nm.

9. The preparation process according to claim 8, characterized in that, The polyvinyl alcohol is a partially hydrolyzed polyvinyl alcohol with a saponification degree of 85%-90%.

10. The preparation process according to claim 9, characterized in that, The polyvinyl alcohol solution also contains boric acid, and the mass of the boric acid is 1% to 5% of the mass of the polyvinyl alcohol.